Associations Between Socio-demographic Characteristics of Food Pantry Clients and Foods Received from Baltimore City Food Pantries (P04-030-19). (13th June 2019) - Adams, Lindsay; Yan, Sally; Ali, Shahmir; Poirier, Lisa; Craig, Hope; Gu, Yuxuan; Gittelsohn, Joel
Abstract: Objectives: The current economic climate across the United States has resulted in a large number of people being reliant on food pantries for long-term, rather than emergency, food assistance. As a result, there is a growing need to evaluate the nutritional quality of foods obtained by food pantry clients, and the factors influencing their selections. We examine the associations between socio-demographic characteristics of food pantry clients, and the healthfulness of foods they receive from food pantries in Baltimore City, Maryland. Methods: We collected data from 7 randomly selected food pantries in Baltimore, Maryland, stratified by size. Clients' socio-demographic information was obtained through interviewer-administered questionnaires ( n = 74). Healthfulness of foods clients received from the pantry was assessed by sorting, weighing, and scoring foods by food group using the Food Assortment Scoring Tool (FAST), with higher scores indicating higher nutritional quality. Results: The average age of clients sampled was 56.4 + 14.5, with 55.4% females and 44.6% males. As for employment status, 36.5% clients are disabled, 27.0% are retired, and 17.5% are employed. Thirty five % reported visiting a pantry once a month, 13.5% twice a month, and 13.5% visited once a week or more. When looking at other forms of food assistance, 57.3% of clients reported using SNAP and 6.6% WIC. When looking at food distribution methods, 44.6% ( n = 32) of clients utilized a client choice pantry. Though the observed relationships are not statistically significant, male clients at client choice pantries had higher mean FAST scores (63.5 + 8.2) than women (60.2 + 7.5) ( P = 0.2). FAST scores of white/Caucasian clients were also higher (68.6 + 6.7) than black/African American clients (60.7 + 7.9) ( P = 0.1). Conclusions: We found no significant sociodemographic factors associated with healthiness of foods obtained by pantry clients in Baltimore. This implies that pantry-level environmental and policy interventions may be more successful than efforts to target specific individuals. Funding Sources: Johns Hopkins University Lerner Center for Public Health Promotion.